Implementasi Metode Naïve Bayes Dalam Penilaian Kinerja Sales Marketing Pada PT. Pachira Distrinusa - Senika, Anis; Rasiban, Rasiban; Iskandar, Dadang (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
This study aims to build an information system that can support companies in making decisions, especially regarding sales assessment at PT. Pachira Distrinusa. This is motivated by the difficulty of determining whether or not a sales person deserves an efficient value, because the system is not yet computerized and employee data documents are piled up. In this study, the data used are assessment data at PT. Pachira Distrinusa and the method used is the Naïve Bayes Classifier algorithm. And to find out how well the Naïve Bayes Classifier algorithm is used in this study, the RapidMiner calculation is used to perform the test. From the test in RapidMiner, the accuracy value is 91.67% and the ROC value is 0.979, which means that the Naïve Bayes Classifier algorithm is very well used in this study. After testing using RapidMiner software and getting the test results, then it is implemented into a system using PHP and MySQL which is designed to predict sales assessments. The prediction results obtained from the system are in accordance with the calculation results obtained from RapidMiner calculations and manual calculations. Based on the research that has been done that the decision support system built can be applied to PT. Pachira Distrinusa so as to make it easier to determine the feasibility of the sales assessment at PT. Pachira Distrinusa efficiently.